PENCEGAHAN RABIES PADA KUCING DENGAN VAKSINASI DAN EDUKASI MASYARAKAT DI KECAMATAN RUNGKUT SURABAYA - Widhowati, Dyah; Rahmaniar, Reina (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
This Community Service aims to prevent rabies in cats and educate the community on how to avoid rabies as a source of transmission from animals. The urgency of this service is based on the fact that Rabies is a disease that can be fatal to humans and warm-blooded animals with a case fatality of 100%, cats can be a source of transmission through bites. The technical implementation of this service consists of several stages. First, education is carried out on the community in the Rungkut area, the second stage is the prevention of rabies with vaccination, then an evaluation of the results and writing of the output of community service is carried out. The target output achieved is the publication of scientific articles in National journals with ISSN. Articles in local electronic mass media, and documentation of the implementation in the form of photos and videos uploaded to the UWKS media center YouTube. This activity is also related to MBKM from 2 aspects: lecturers and students. Lecturers have the opportunity to implement their scientific knowledge to be applied in society, this is related to the Main Work Indicator (IKU) 5 program. Meanwhile, students can participate in activities outside the campus that support the achievement of IKU 2. This activity successfully carried out rabies vaccination on 60 owned domestic cats and was accompanied by education about rabies as a preventable disease.